A review of nanoparticle synthesis methods, classifications, applications, and characterization - Murtala, Namakka; Md. Rezaur, Rahman; Khairul Anwar, Mohamad Said; Mohammad, Abdul Mannan; Abdul Majed, Patwary (Elsevier Science, Ltd., 2023)
Nanoparticles, at the convergence of science and technology, have rapidly evolved and continue to revolutionize numerous fields. Research areas that make use of contemporary advances in nanotechnology include wastewater treatment, such as the recent use of nanocomposites in membrane surfaces. However, membrane fouling associated with its surface hydrophobic properties is a major setback bedeviling effective removal of carcinogenic and non-biodegradable chemicals presents in wastewater discharges. Nanoparticles with controlled morphologies when incorporated into membrane surfaces impart hydrophilicity and enable efficient membrane-water interactions. There are many synthesis methods of nanoparticles, ranging from physical to chemical to green synthesis, rendering the selection of suitable methods that enable control over the morphological structure of the synthesized material highly challenging. Herein, we provide a comprehensive review of nanoparticles, synthesis methods, characterization techniques, and their multifaceted applications. The choice of suitable methods depends on their ability to produce nanoparticles with controlled morphologies, perspicuous technology, and low energy requirements compared to other methods. Factors such as pH concentration and calcination temperature are found to influence morphological structure. The article also discusses the synthesis of nano oxides like titanium dioxide (TiO2), silicon dioxide (SiO2), and their composites. The review is designed to facilitate informed decisions and to serve as a beneficial reference for researchers as well as professionals, fostering the transfer of knowledge, multidisciplinary collaboration, and novel advances in the dynamic and evolving domain of nanoparticles.